A Qualitative Study Exploring Barriers and Facilitators of Enrolling Underrepresented Populations in Clinical Trials and Biobanking - Davis, Terry C.; Arnold, Connie L.; Mills, Glenn; Miele, Lucio (Frontiers in Cell and Developmental Biology, 2019)
Disparities exist in enrollment in clinical trials and biorepositories among adults with low socioeconomic status, racial and ethnic minority groups and individuals who live in rural areas. Diverse participation is necessary to identify the most effective treatments in different groups. The purpose of this study was to use qualitative methods to identify factors that may affect the likelihood that members of underrepresented groups choose to participate in clinical trials and/or biobanking. We conducted 14 focus groups and 7 telephone interviews in urban and rural areas of Louisiana to: 1) identify barriers and facilitators to participation; and 2) elicit input in crafting clear, culturally appropriate language and recruitment strategies. Of 103 participants, 25 were safety-net healthcare providers, 18 were primary care or oncology clinic patients, and 60 were members of social and faith-based groups. Patients and community participants were English-speaking, 79% were African American, 81% were female and 24% lived in rural areas. Barriers to participation identified were lack of knowledge about clinical trials and biobanks; limited specific information and access to participation, trust and privacy concerns about clinical trials and biobanking Facilitators included: altruism, high interest in medical research particularly studies that might benefit them or their families; plain language, culturally appropriate information; convenient access to studies; and input of a trusted provider. Results of this study can inform the development of education materials and strategies to increase participation of underrepresented groups in clinical trial and biobanking.